Efektivitas Program Kelompok Usaha Bersama Dalam Meningkatkan Kesejahteraan Masyarakat Pada Kecamatan Lapandewa Kabupaten Buton Selatan - Kambolong, Makmur; Alam, Syamsul; Maludin, Maludin (REZ PUBLICA, 2021)
The purpose of this study was to determine the effectiveness of the Joint Business Group in improving the welfare of the Community in the Lapandewa sub-district, South Buton Regency The method used in this research is qualitative descriptive research with data collection techniques using observation, interviews and documentation techniques.The results of this study indicate that the effectiveness of the Joint Business Group program in improving community welfare in Lapandewa District, South Buton Regency is still not effective. this can be seen from the three indicators of effectiveness which include program socialization, counseling on business skills to KUBE recipient communities as well as, assistance to established programs that have not been implemented properly, and indicators of community welfare which include income level, education level and health level are still not implemented properly. Therefore, it can be concluded that the effectiveness of the Joint business group in improving welfare is still not well implemented in Lapandewa District, South Buton Regency.